FEATURES OF USING A COMPUTER B EDUCATIONAL PROCESS OF HIGHER SCHOOL - N.V. Vyshnevska (Academy of Cognitive and Natural Sciences, 2006)
The author of the article highlights the effectiveness to use a computer in educational process in higher educational establishment.